2023
DOI: 10.3390/su15043365
|View full text |Cite
|
Sign up to set email alerts
|

Toward 30 m Fine-Resolution Land Surface Phenology Mapping at a Large Scale Using Spatiotemporal Fusion of MODIS and Landsat Data

Abstract: Satellite-retrieved land surface phenology (LSP) is a first-order control on terrestrial ecosystem productivity, which is critical for monitoring the ecological environment and human and social sustainable development. However, mapping large-scale LSP at a 30 m resolution remains challenging due to the lack of dense time series images with a fine resolution and the difficulty in processing large volumes of data. In this paper, we proposed a framework to extract fine-resolution LSP across the conterminous Unite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…The ESTARFM and EVI2 models accurately forecast the spatial distribution features of the red bands and NIR bands. The fusion of images using the proposed reference image selection rule yields similar results to the actual ones [189].…”
Section: Climate Warmingmentioning
confidence: 54%
See 1 more Smart Citation
“…The ESTARFM and EVI2 models accurately forecast the spatial distribution features of the red bands and NIR bands. The fusion of images using the proposed reference image selection rule yields similar results to the actual ones [189].…”
Section: Climate Warmingmentioning
confidence: 54%
“…Large-scale multispectral and multitemporal observation data may be obtained using remote sensing, making it a useful technique for comprehensive monitoring of glaciers, forest fires caused by climate change and land surface phenology [187][188][189]. Satellite-retrieved land surface phenology (LSP) is vital for monitoring the ecological environment as well as human and societal sustainable development since it plays a key role in energy exchange, the Earth's water cycle, and the carbon balance [190,191].…”
Section: Climate Warmingmentioning
confidence: 99%
“…The experimental results showed that the accuracy of direct vegetation index data fusion was higher, and in-depth studies such as surface vegetation cover can be conducted on this basis. The existing studies mostly applied the fusion model to Landsat and MODIS data [34], and the study of grassland cover change and toxic weed invasion in the TRHR also focused on medium-and low-resolution remote sensing data [35]. In contrast, Sentinel-2 had a higher spatial resolution compared to Landsat data, and the accuracy of monitoring the surface vegetation cover and change was also higher.…”
Section: Discussionmentioning
confidence: 99%